Integrated approach of whole-genome analysis, toxicological evaluation and life cycle assessment for pyrene biodegradation by a psychrophilic strain, Shewanella sp. ISTPL2. (15th January 2021) - Rathour, Rashmi; Medhi, Kristina; Gupta, Juhi; Thakur, Indu Shekhar
Abstract: Polycyclic aromatic hydrocarbons (PAHs) such as pyrene are universal contaminants existing in the environment which have known cancer-causing and mutagenic characteristics. A psychrophilic bacterial strain Shewanella sp. ISTPL2 was isolated from the sediment sample collected from the Pangong lake, Jammu & Kashmir, India. In our previous study, the pyrene degradation potential of the ISTPL2 strain was studied in both mineral salt media as well as in soil artificially spiked with different concentrations of pyrene. Whole-genome sequencing of ISTPL2 strain in the current study highlighted the key genes of pyrene metabolism, including alcohol dehydrogenase and ring hydroxylating dioxygenase alpha-subunit. Pyrene cytotoxicity was evaluated on HepG2, a human hepato-carcinoma cell line. The cytotoxicity of the organic extract decreased with the increasing duration of bacterial treatment. To develop a more sustainable biodegradation approach, the potential impacts were evaluated for human health and ecosystem using life-cycle assessment (LCA) following the ReCiPe methodology for the considered PAH. The results implemented that global warming potential (GWP) had the highest impact, whereas both ecotoxicity and human toxicity had least from this study. Graphical abstract: Image 1 Highlights: Genes responsible for pyrene degradation were predicted through WGS. Pyrene degrading genes such as RHDα identified vital in pyrene degrading bacteria. The MTT assay showed a reduction in bacterial treated pyrene cytotoxicity. LCA results illustrated that GWP had the highest environmental impact. Pyrene biodegradation process implied neither environmental nor human health load.